Fabrication and testing of GLARE specimens - Tan, Khim Yang (2016)
The report presents the experimental results of the investigation of the effect of composition and lay-up sequence on the mechanical properties of GLARE specimens and related hybrid composites. Tensile tests and Quasi-static indentation tests were performed to evaluate the performance of the fabricated specimens. The first chapter of the report studies the Quasi-static indentation (QSI) response of hybridised composition of acrylic (PMMA) and polycarbonate (PC). A comparison of load characteristics was drawn between samples of different Polycarbonate Volume Fraction (PVF) and thickness. The load-displacement and energy profile curve were obtained by the varying configuration of the hybrid composite. It was found that the stacking sequence and the thickness of each individual layer has significant effect on the damage mechanism of the laminate. Extensive damage in the form of delamination, radial and circumferential cracks were observed in all samples. The next chapter of the report focuses on the Quasi-static indentation characteristics in glass fibre laminates. Changes in the orientation and stacking sequence of the woven glass fibre fabric was found to have an impact on the damage initiation and the extent of damage within the laminates. The last chapter of the report investigates the damage performance of GLARE specimen in Quasi-static indentation tests. The load-displacement and energy absorption characteristics were compared with varying stacking sequence, woven fabric layup and thickness. The 2/1 stacking sequence was found to behave in a more ductile manner than the 1/1 configuration, but possess lower peak load and energy absorption capacity. In contrast, samples with 1/1 stacking sequence demonstrate the ability delay the onset of the final failure laminate. In addition, it was found that for both 1/1 and 2/1 stacking sequence, the samples with Quasi-isotropic (QI) layup display lowered indentation damage tolerance than its counterparts.